Theoretical and practical bases of religious expertise in the Republic of Kazakhstan (Eurasian Journal of Religious Studies, 2023)
The article deals with the main theoretical issues and functional mechanisms of the concept of religious expertise. To analyze this issue, the main scientific conclusions about the concept, goals and scientific and methodological foundations of religious expertise in international practice were differentiated. The limited number of scientific articles and research papers on this topic in domestic research determines the relevance of the identified problem and the need to systematize this area. Today, in the Republic of Kazakhstan, the field of religious studies expertise is one of the new directions. This area, implemented in the country for more than ten years, is a public service for legal entities and individuals. The practical aspects of the implementation of religious studies expertise are determined by the state within the framework of legislation in the field of religion. However, at the domestic level, it is necessary to solve the problem of determining the theoretical and conceptual categories of religious studies expertise, systematizing the main scientific methods. Since, in the course of studying foreign and domestic experience, it was found that the methodology for conducting religious expertise has not been developed at a sufficient level.
Keywords: religious expertise; scientific neutrality; religious activity; freedom of religion; religious extremism